Effects of palm oil derived tocotrienol rich fraction (TRF) on coronary risk markers: in vitro and in vivo studies / Suhaila Abd Muid - Abd Muid, Suhaila (2008)
Tocotrienol is one of the vitamin E compounds which have potent anti-oxidant activity leading to reduction in oxidative stress and inflammation. Oxidative stress and inflammation are now emerging as pivotal factors in the pathogenesis of atherosclerosis and coronary artery disease (CAD). However, optimal concentrations of palm oil derived tocotrienol rich fraction (TRF) that may lead to reduction of oxidative stress and inflammation in in vitro and in vivo studies are still unclear. The objectives of this study were to determine the optimal concentrations of TRF which leads to the highest antioxidant activity and reduction of inflammation markers in vitro and to study the effects of palm oil derived TRF vitamin E capsules (Palmvitee) contained low dose tocotrienol on oxidative stress in patients with non-familial hypercholesterolaemia (NFH). Antioxidant activities were assessed by Ferric thiocyanate (FTC), 1,1-diphenyl-2picrylhydrazyl (DPPH) radical scavenging activities and dichlorofluorescein diacetate (DCFHDA) assays. Supernatant of stimulated endothelial cells was measured for the production of inflammatory markers [e-selectin, p-selectin, soluble intercellular cell adhesion molecule-1 (sICAM-1), soluble vascular cell adhesion molecule-1 (sVCAM-1) and inter leukin-6 (IL-6)]. Sixty-six patients with NFH (38 males, 28 females, age ± SD age = 46.9 ± 9.4 years) were recruited and randomised to 3 treatments arm, which were palmvitee 300 mg/day (NFHe), atorvastatin 10 mg/day plus placebo (NFHsp) or atorvastatin 10 mg/day plus palmvitee (NFHse). Fasting serum lipids (FSL), oxidised LDL (ox-LDL), malondialdehyde (MDA) and 8-epi-PGF2α were measured at baseline (BL) and 2 weeks, 12 weeks and 36 weeks post-randomisation. Normocholesterolaemic (NC) subjects were recruited in parallel. In the FTC assay, TRF at concentrations 10 and 100 µg/ml showed the highest percentage (%) of inhibition, 96.4 ± 0.2% and 96.3 ± 0.2% respectively. In the DPPH assay, optimal TRF concentration was observed at concentration 62.5 µg/ml with the highest % inhibition (85.2 ± 0.8%). Lowest % increase of DCF fluorescence production was shown by induced RAW 264.7 cells incubated with 88 µg/ml TRF concentration and it was significantly lower than DCF fluorescence produced by RAW 264.7 cells incubated with inducer (lipopolysaccharides and interferon gamma) alone , 95.0 ± 1.4% vs. 194 ± 18.5%, p<0.05. -The results from the DPPH and DCFHDA assay were consistent with the findings from the .FTC method which reported optimal TRF concentration within the range of 10-100 µg/ml, Optimal TRF concentrations leading to maximal inhibition of e-selectin , p-selectin, sICAM-1 , sVCAM-1 and IL-6 in stimulated endothelial cells were 0.8, 0.4, 0.8, 3.4 and 0.2 µg/ml, with percentage inhibition of 88.0 ±2.0%, 88.0 ±0.1%, 55.0 ±3.0%, 75.0 ±4.0% and 56.0 ±12.0%, respectively. NFHe group showed neutral effects on FSL, but reductions in MDA (p<0.005), ox-LDL (p<0.05) and 8-epi-PFGF2α (p<0.05) levels at 12 weeks compared to BL. NFHsp and NFHse groups showed similar reductions in 'Fe and LDL at 2 weeks (p<O.OOO 1) compared to BL. TO level was also reduced at 2 weeks in both NFHsp (p<O.O 1) and NFHse (p<0.005) groups compared to BL. NFHsp and NFHse